Implementasi Naïve Bayes Dalam Pemilihan Jenis Bahan Pembuatan Meja - Amin Joko Susilo; kustanto kustanto kustanto; Dwi Remawati (STMIK Sinar Nusantara, 2023)
Wood is a very decisive main element in the furniture industry or other wood crafts. Furniture was originally an industry of furniture crafts and wood carvings, so that the furniture products produced highlighted the effect of art. To determine whether a wood is suitable or not as a furniture material, systematic and accurate calculations are needed in order to obtain the right decision making. From this problem the researcher implemented the Naïve Bayes method to classify the quality level of wood based on the probability of wood. This makes it easier for table manufacturers to choose wood based on the texture of the wood. The purpose of this study is to implement the Naïve Bayes method to classify the quality level of wood based on the probability of wood. The criteria used in this study include: wood texture, wood quality, wood age, wood diameter. The results of this study are in the form of a recommendation that the type of material was teak wood, the age of the wood was still young, the quality of the wood was good, the diameter of the wood was sufficient and the texture of the wood was smooth, the quality of the wood was suitable for use for raw materials for making tables